Body weight dissatisfaction and its correlates among Brazilian adolescents - Christofaro,Diego G.D. (2015)
OBJECTIVE: This study examined the prevalence of body weight dissatisfaction and its relationship to physical activity and nutritional status in adolescents. METHOD: The study enrolled 2,288 adolescents. The dependent variable was body weight dissatisfaction. The independent variables were physical activity and nutritional status. The confounders were gender, and economic condition. Associations between dependent and independent variables were analyzed through the chi-square test and the magnitude of the associations was estimated by Poisson regression. RESULTS: A total of 56.6% of adolescents were not satisfied with their weight, with 17.9% wanting to increase it, while 37.7% wanted to decrease their weight. In boys and girls, body weight dissatisfaction was associated with nutritional status, abdominal obesity and physical activity in crude analyses. After adjustments, nutritional status and abdominal obesity remained significantly associated to body weight dissatisfaction in both sexes. CONCLUSION: A high prevalence of body weight dissatisfaction was identified, which was associated with the nutritional status and abdominal obesity in adolescents.